Risk Factors for Phenoconversion in Rapid Eye Movement Sleep Behavior Disorder. Issue 3 (24th January 2022) - Zhang, Hui; Iranzo, Alex; Högl, Birgit; Arnulf, Isabelle; Ferini‐Strambi, Luigi; Manni, Raffaele; Miyamoto, Tomoyuki; Oertel, Wolfgang H.; Dauvilliers, Yves; Ju, Yo‐EI; Puligheddu, Monica; Sonka, Karel; et al.
Abstract : Objective: This study was undertaken to follow up predictive factors for α‐synuclein–related neurodegenerative diseases in a multicenter cohort of idiopathic/isolated rapid eye movement sleep behavior disorder (iRBD). Methods: Patients with iRBD from 12 centers underwent a detailed assessment for potential environmental and lifestyle risk factors via a standardized questionnaire at baseline. Patients were then prospectively followed and received assessments for parkinsonism or dementia during follow‐up. The cumulative incidence of parkinsonism or dementia was estimated with competing risk analysis. Cox regression analyses were used to evaluate the predictive value of environmental/lifestyle factors over a follow‐up period of 11 years, adjusting for age, sex, and center. Results: Of 319 patients who were free of parkinsonism or dementia, 281 provided follow‐up information. After a mean follow‐up of 5.8 years, 130 (46.3%) patients developed neurodegenerative disease. The overall phenoconversion rate was 24.2% after 3 years, 44.8% after 6 years, and 67.5% after 10 years. Patients with older age (adjusted hazard ratio [aHR] = 1.05) and nitrate derivative use (aHR = 2.18) were more likely to phenoconvert, whereas prior pesticide exposure (aHR = 0.21–0.64), rural living (aHR = 0.53), lipid‐lowering medication use (aHR = 0.59), and respiratory medication use (aHR = 0.36) were associated with lower phenoconversion risk. Risk factors for those converting to primary dementia and parkinsonism were generally similar, with dementia‐first converters having lower coffee intake and beta‐blocker intake, and higher occurrence of family history of dementia. Interpretation: Our findings elucidate the predictive values of environmental factors and comorbid conditions in identifying RBD patients at higher risk of phenoconversion. ANN NEUROL 2022;91:404–416